Assessment of Local Scour Patterns Around Bridge Piers and Optimal Placement in a 180-Degree Bend Using Experimental and Finite Volume Methods - Pooya Biranvand; Hamidreza Vossoughifar; Milad Khorani; Hamzeh Heidari Soureshjani (مدل‌سازی پیشرفته در مهندسی عمران, 2025)
In curved channels, secondary flows arise due to the balance between centrifugal and gravitational forces, causing a vertical redistribution of flow that significantly alters bed shear stress and sediment transport. The introduction of hydraulic structures such as bridge piers further intensifies the complexity of flow patterns and local scour processes. This study investigates the effects of pier placement in a 180-degree bend of a U-shaped channel using both experimental and numerical approaches. Six angular pier positions (0°, 30°, 60°, 90°, 120°, and 150°) were analyzed, with positions at 60° and 150° used for model validation. The study employed the finite volume method (FVM) via Fluent software and validated the results against physical experiments using ADV-based velocity profiling and bed morphology measurements. Results show that the magnitude of bed material removal is greater within the bend compared to straight reaches due to intensified helical flows. Notably, the most severe sediment deposition occurred at 30° and 60°, while reduced scour was observed at 150°. Based on flow behavior and scour depth analysis, optimal pier locations were identified to be within 0°–30° and 90°–180°, balancing flow stability and minimizing bed degradation.